1978
DOI: 10.1111/j.1365-2265.1978.tb02159.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inter‐relationship of Thyroid Hormones, Vitamin a and Their Binding Proteins Following Acute Stress

Abstract: The effects of surgical stress on the metabolism of the retinol-binding-protein-thyroxine-binding-prealbumin complex were investigated. The immediate postsurgical period was characterized by a rapid decline in the serum concentration of retinol, retinol binding protein and triiodothyronine and an increase in the 24 h urinary excretion of retinol, retinol-binding-protein and thyroxine. Similar, but less pronounced, changes were seen in other subjects suffering acute myocardial infarction but were not observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…However, these studies have had difficulty assessing which is the prime driver because of the close interaction between VA deficiency and infection-induced inflammation. Even clinical studies, in which serial measurements of plasma retinol or urinary RBP have been used to monitor the effect of infection-induced inflammation, have not clearly determined the cause and consequences of hyporetinolemia (31,32). Experimental studies in animals have shown without exception that plasma retinol can be reduced by a variety of immune stressors ranging from viral infections and turpentine injections to prolonged immobilization (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have had difficulty assessing which is the prime driver because of the close interaction between VA deficiency and infection-induced inflammation. Even clinical studies, in which serial measurements of plasma retinol or urinary RBP have been used to monitor the effect of infection-induced inflammation, have not clearly determined the cause and consequences of hyporetinolemia (31,32). Experimental studies in animals have shown without exception that plasma retinol can be reduced by a variety of immune stressors ranging from viral infections and turpentine injections to prolonged immobilization (32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…However, infection has pronounced effects on thyroid hormones, since they are transported in the blood by the negative acute-phase protein, transthyretin (TTR). The synthesis of TTR is markedly suppressed by infection (Ramsden et al 1978;Dickson et al 1982), thus thyroid hormone levels measured in communities where infection is common should be interpreted with caution. Whether such measurements can be better assessed using other acute-phase proteins to detect infection, as suggested for retinol, remains to be investigated.…”
Section: Mineralsmentioning
confidence: 99%
“…Evidence has been accumulated to indicate that the metabolism of vitamin A is modulated under various nutritional, hormonal and physiological conditions (2)(3)(4)(5)(6)(7)(8)(9). Many studies along these lines have been carried out by following changes in the tissue distribution of cold or radioactive retinoids.…”
Section: Abstract Vitamin A-depletion Vitamin A-free Diet Tissue Vmentioning
confidence: 99%